Pan-cancer characterisation of microRNA across cancer hallmarks reveals microRNA-mediated downregulation of tumour suppressors - Andrew Dhawan; Jacob G. Scott; Adrian L. Harris; Francesca M. Buffa (Nature Communications, 2018)
miRNAs have emerged as regulators of diverse biological processes including cancer. Here the authors present an extended pan-cancer analysis of the miRNAs in 15 epithelial cancers; integrating methylation, transcriptomic and mutation data they reveal alternative mechanisms of tumour suppressors’ regulation in absence of mutation, methylation or copy number alterations.